THE INFLUENCE OF BRAND EQUITY, INFLUENCER EQUITY, AND SOCIO-DEMOGRAPHICS ON PURCHASE INTENTION AS A MARKETING STRATEGY FOR SAMSUNG X BTS IN INDONESIA - Vanni Fadilla (Human Resource Management Studies, 2024)
This study aims to determine : (1) The effect of Brand Equity on Purchase Intention. (2) The effect of Influencer Equity on Purchase Intention. (3) The effect of Socio-Demographics on Purchase Intention. The population on this study are people who have never purchased or used a Samsung X BTS. The number of samples in this study were 230 respondents. The data in this study were collected through an online questionnaire with google form media and data processing was carried out using SmartPLS software. The results of this study indicate that : (1) Brand Equity has a significant positive effect on Purchase Intention. (2) Influencer Equity has a significant positive effect on Purchase Intention. (3) Socio-Demographics no has a significant positive effect on Purchase Intention.